2013
DOI: 10.1371/journal.pone.0053211
|View full text |Cite
|
Sign up to set email alerts
|

Old Players with a Newly Defined Function: Fra-1 and c-Fos Support Growth of Human Malignant Breast Tumors by Activating Membrane Biogenesis at the Cytoplasm

Abstract: A shared characteristic of tumor cells is their exacerbated growth. Consequently, tumor cells demand high rates of phospholipid synthesis required for membrane biogenesis to support their growth. c-Fos, in addition to its AP-1 transcription factor activity, is the only protein known up to date that is capable of activating lipid synthesis in normal and brain tumor tissue. For this latter activity, c-Fos associates to the endoplasmic reticulum (ER) through its N-terminal domain and activates phospholipid synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…It is likely that a similar molecular paradigm contributes to cSCC which shares many similarities with HNSCC in pathogenesis [17]. Our findings are also in line with earlier studies linking cytoplasmic c-Fos and FRA1 to the synthesis of membrane lipid polyphosphoinositides including PIP1 and PIP2 [31, 32], components essential for PI3K activation. In agreement with a role of FRA1 in membrane lipid synthesis, FRA1 was located on the cell membrane of tumor marginal cells (Data not shown).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is likely that a similar molecular paradigm contributes to cSCC which shares many similarities with HNSCC in pathogenesis [17]. Our findings are also in line with earlier studies linking cytoplasmic c-Fos and FRA1 to the synthesis of membrane lipid polyphosphoinositides including PIP1 and PIP2 [31, 32], components essential for PI3K activation. In agreement with a role of FRA1 in membrane lipid synthesis, FRA1 was located on the cell membrane of tumor marginal cells (Data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, little is known about the role of FRA1 and the mechanisms mediating its function in HNSCC. Recently, it has been shown that FRA1 acts outside the nucleus to regulate membrane lipid synthesis in an AP-1-independent manner [31, 32]. In this study, we demonstrate that gene silencing of FRA1 impaired growth and migration of multiple HNSCC cell lines.…”
Section: Introductionsupporting
confidence: 63%
“…We have already proved the involvement of Fra-1 in the proliferation of breast cancer cells by increasing phospholipid labeling (38). Here, we also confirmed that at least for PAP I, Fra-1 is able to increase enzyme activity as c-Fos does.…”
Section: Discussionsupporting
confidence: 82%
“…It mediates the anti-apoptotic response to hypoxic conditions and contributes to resistance to chemo-and radiotherapy in colon cancer cells (37), while it influences pivotal regulators of cell proliferation, migration and survival involved in melanoma progression (38) as well as in the carcinogenesis of the respiratory epithelium (39). c-Fos has been found to be associated with lipid-and phospholipid synthesis in several cell types (40) and activates biogenesis in certain types of tumor cell to support tumor growth (41,42). c-Jun is a critical transcription factor involved in major cell-biological activities, including cell proliferation, apoptosis, angiogenesis and invasiveness by specific regulation of epidermal growth factor receptor, keratinocyte growth factor, cyclin D1, p53, proliferin and CD44 (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%